2002
DOI: 10.1046/j.1365-2648.2000.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Demands of Immigration Scale with Taiwanese–Chinese immigrants: a pilot study

Abstract: Analyses suggest that the Chinese version is easy to read and understand. The internal consistency and test-retest reliability are satisfactory. This scale could be used with Taiwanese-Chinese immigrants as a generic measure of immigration-related distress. Nonetheless, three main problems with its use with Taiwanese-Chinese immigrants and Chinese immigrants at large are revealed in the study. Each problem is discussed. Suggestions for further development of the Chinese DI Scale are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…Similar patterns of missing data on occupation-related items were documented by a study of Taiwanese-Chinese immigrants in the US (Tsai 2002). Aroian et al (2008) also found that questions regarding job adjustment were not relevant to populations that were usually not employed outside the home, such as Arab Muslim women.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar patterns of missing data on occupation-related items were documented by a study of Taiwanese-Chinese immigrants in the US (Tsai 2002). Aroian et al (2008) also found that questions regarding job adjustment were not relevant to populations that were usually not employed outside the home, such as Arab Muslim women.…”
Section: Discussionsupporting
confidence: 78%
“…The DI scale was used among several ethnic groups. While the original factor structure was replicated among some immigrant groups, such as Arab immigrants, (Aroian et al 2007), a different factor structure was found in Taiwanese-Chinese immigrants (Tsai 2002). To date, the DI scale has not been used among Korean immigrants, therefore the factor structure, reliability and validity need to be established with this population.…”
Section: Introductionmentioning
confidence: 96%
“…A composite measure was formed by computing the mean, producing reliability of α = 0.885. The DIS showed high internal consistency in a sample of adult Taiwanese-Chinese immigrants to the U.S. (Tsai, 2002). The DIS also demonstrated reliability and validity within the current sample of female Korean immigrants (Ding et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…These six areas of immigration adjustment have been documented in the literature and form the basis of the six subscales in the DI scale used in this study 14–17 . To quantify psychological stress experienced by immigrants during adjustment to a new country, the DI scale was developed to measure demands associated with immigration 15 .…”
Section: Introductionmentioning
confidence: 99%
“…To quantify psychological stress experienced by immigrants during adjustment to a new country, the DI scale was developed to measure demands associated with immigration 15 . This scale has been used in studies with Polish immigrants, former Soviet Union immigrants, Brazilian women, Russian immigrants, Taiwanese immigrants, Indian nurses, and Canadian and Filipino nurses 12,13,15,16,18,19 . In these studies, all immigrant groups have reported varying amounts and sources of immigration demands.…”
Section: Introductionmentioning
confidence: 99%